(untitled) (The Thinker, 2024)
It took 45 years between when the First Ordinary Session of the then Organisation of African Unity (OAU) [now the African Union] declared Africa a denuclearized zone in July 1964 and when the African Nuclear-Weapon-Free Zone Treaty (Treaty of Pelindaba) entered-into-force on 15 July 2009. This article briefly describes the provisions of the Treaty and then provides some examples of how activism assisted this process, before concluding on the possible reasons for the long delay for the Treaty of Pelindaba to be inscribed into international law.